TINJAUAN UMUM TENTANG KRIMINOLOGI, KENAKALAN ANAK, BALAPAN LIAR DAN PENANGGULANGAN KENAKALAN - Ni Putu Rai Yuliartini (Ganesha Civic Education Journal, 2022)
Overcoming illegal racing through penal means is one of the functionalizations of penal policy, especially at the application stage (judicative policy) carried out by law enforcement officials, one of which is the police. Efforts to tackle illegal racing in Singaraja City through penal facilities focus more on the repressive nature after illegal racing occurs which is an effort to prosecute and enforce the law against perpetrators of illegal racing in accordance with applicable laws and regulations. Through Non-Penal Means Efforts to deal with illegal racing through non-penal means are more focused on the nature of prevention before wild racing occurs, namely through pre-emptive efforts and preventive efforts. The implementation of these pre-emptive and preventive efforts is based on the Obedient and Sympathetic Operation Plan (RENOPS) of the Buleleng Police. RENOPS Compliance and Sympathy of the Buleleng Police is carried out by prioritizing pre-emptive activities through traffic education and counseling, and preventive actions through regulation, guarding, escorts and traffic patrols to prevent activities that disturb Traffic Traffic Traffic, one of which is illegal racing.